La Gravure Suédoise Contemporaine. - NUNSKU, Stockholm (La Louvière : Centre de la Gravure et de l'Image Imprimée, 1989)
Anshelm, Kristina ; Arkoo, Jordi ; Brusewitz, Björn ; Elggren, Leif ; Engström, Urban ; Eriksson, Leif ; Gram, Lennart ; Gripenholm, Ulf ; Hamne, Curt ; Hanspers, Olle ; Hurtig, Ingvar ; Johansson, Sven-Erik ; Karlsson, Igge ; Larson, Gunnar ; Lindeberg, Lars ; Lundberg, Bertil ; Manker, Jan ; Molin, Brita ; Olausson, Leif ; Pettersson, Rune ; Puryear, Rachelle ; Pyk, Madeleine Rosa ; Svedlund, Yngve ; Trotzig, Ulf ; Arlin, Richard
La Gravure Suédoise Contemporaine, Centre de la Gravure et de l'Image Imprimée, La Louvière, 7 avril - 11 juin 1989
Frans
kunstcatalogus
Keywords: Zweden